Philippine medical thesaurus on anatomy embryonic structure and urogenital system - Roque, Arvin C.; Tarlit, Rodolfo Y. (Quezon City Institute of Library Science, University of the Philippines Diliman, 2003)
This study sought to 1.) To collect Tagalog index terms for the Embryonic Structure and Urogenital System, components of the Philippine Medical Thesaurus; 2.) To organize these index terms according to their equivalent, associative and hierarchical relationships; 3.) To map the Tagalog terms to the MeSH terms. In the construction of the thesaurus, the top-down approach or deductive method was employed. Translation work was done through the use of dictionaries and advice of experts and informants, selected by purposive sampling.
The results showed that thesaurus construction and translation were complex processes. It is also shown that about 57 of the English terms had no equivalent Tagalog terms. It is recommended that 1.) Future researchers should create well-planned strategies before venturing into translation and thesaurus construction of this magnitude; 2.) Conduct an in-depth study of language use and its complexities, to be able to determine the appropriate terms to be used as preferred terms; 3.) Cultivate and sustain collaboration among respondents and researchers to avoid miscommunication and to reduce the time spent in gathering data. Good respondent-researcher rapport proved to be one of the most important aspects in achieving the objectives of the project; 4.) To revalidate the authoritativeness of the dictionaries. Comprehensiveness and thoroughness of materials should be included as criteria in the prioritization of dictionaries as tool for translation.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: Subject headings, Filipino -- Medicine; Subject headings, Filipino -- Genitourinary organs; Filipino language -- Medical Filipino